Surgical treatment of dural arteriovenous fistulas of the petrous apex - Westermaier, Thomas L.; Bendszus, Martin (World neurosurgery, 2012)
Objective To report a series of four patients with dural arteriovenous fistulas (DAVF) at the petrous apex with drainage into the deep cerebral venous system and the surgical treatment employed. Methods Four patients with DAVFs at the petrous apex are presented. One patient was admitted with cerebral hemorrhage from a second occipital DAVF, and three patients had cranial nerve palsies. All fistulas were type III or IV according to Cognard's classification with venous drainage into the deep cerebral veins. Results Transarterial embolization was performed in two patients. Partial transarterial embolization was possible resulting in a marked flow reduction. In one further patient, surgical treatment via a subtemporal approach was attempted, but complete obliteration of the fistula was impossible. In all patients, complete occlusion of the DAVF was achieved by surgical interruption via a standard retrosigmoid approach to the cerebellopontine angle. Conclusions Treatment of these type III or IV DAVFs was indicated. The fistulas were supplied by multiple meningeal feeders originating from the external and internal carotid and vertebral arteries. Preoperative transarterial embolization resulted in significant flow reduction. Complete cure at low risk was achieved by interruption of the venous drainage via a retrosigmoid approach.